2010
DOI: 10.2110/jsr.2010.025
|View full text |Cite
|
Sign up to set email alerts
|

Sediment Distribution and Architecture Around a Bathymetrically Complex Basin: An Example from the Eastern Champsaur Basin, Se France

Abstract: The Eocene to Oligocene deposits of the Alpine Foreland Basin of Southeast France include a series of partially preserved, originally interconnected turbidite-filled subbasins. Within these remnants, well-constrained interpretations of sediment architectures have been developed by many geologists of the last five decades which are used to resolve both intrabasinal and interbasinal filling histories (e.g., the Annot, Grand Coyer, Col de la Cayolle, and Trois É vêchés subbasins). However, little is known about t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 49 publications
1
22
0
Order By: Relevance
“…2a) lies in high mountain country adjacent to the Col des Pisses (44°43'57"N, 06°19'38"E) with exceptional preservation of bed-scale textures. Palaeoflow regionally was from south to SSE (Vinnels et al 2010). Sparse tool-marks from the base of beds in the studied section accord with this.…”
Section: Assessing Syndepositional Deformationsupporting
confidence: 67%
See 1 more Smart Citation
“…2a) lies in high mountain country adjacent to the Col des Pisses (44°43'57"N, 06°19'38"E) with exceptional preservation of bed-scale textures. Palaeoflow regionally was from south to SSE (Vinnels et al 2010). Sparse tool-marks from the base of beds in the studied section accord with this.…”
Section: Assessing Syndepositional Deformationsupporting
confidence: 67%
“…For illustrative purposes, an example is chosen here from the Eocene-Oligocene Champsaur sandstone of the French Alps, a system described most recently by Vinnels et al (2010). The succession consists of interbedded turbidite sandstones and mudstones that constitute the down-system equivalent of the extensively studied Annot system of SE France (Joseph & Lomas 2004).…”
Section: Assessing Syndepositional Deformationmentioning
confidence: 99%
“…There is increasing evidence that gravity flow transformations, from turbidity flow to cohesive and laminar flow, are the dominant bed type in the distal ends of submarine fan systems and the fringes of individual lobes (e.g., Barker, Haughton, McCaffrey, Archer, & Hakes, 2008;Fonnesu et al, 2018;Grundvåg et al, 2014;Haughton et al, 2003Haughton et al, , 2009Hodgson, 2009;Ito, 2008;Kane & Pontén, 2012;Lowe & Guy, 2000;Pierce et al, 2017;Spychala, Hodgson, & Lee, 2017;Sylvester & Lowe, 2004;Talling et al, 2004). However, they are not exclusively restricted to the distal parts and can also be present in proximal areas of lobes, where they are interpreted as the product of enhanced erosion and flow deceleration due to processes occurring in the channel-lobe transition and due to basin confinement (e.g., Fonnesu et al, 2018;Haughton et al, 2009;Ito, 2008;Jackson et al, 2009;Mueller et al, 2017;Patacci et al, 2014;Sylvester & Lowe, 2004;Terlaky et al, 2016;Vinnels, Butler, McCaffrey, & Lickorish, 2010).…”
Section: Bed Type Associations (Bta)mentioning
confidence: 99%
“…However, Athmer et al (2010) concluded that the investigation of the behavior of density-stratified flows in the presence of seafloor topographic constraints would be useful, thus implying that the interaction of stratified flows with topographic features can lead to distinctive depositional patterns. Flowstripping processes, although as originally defined should be restricted to the channel-bend environment (Piper and Normark 1983), have been recently singled out to indicate a larger-scale flow detachment in the presence of local topographic features (Mutti et al 2002;Sinclair and Tomasso 2002;Tomasso and Sinclair 2004;Bernhardt et al 2011;Vinnels et al 2010). The makeup of the Villafranca lobe complex can therefore also be explained as resulting from the different behavior of two portions of single turbidity currents that, at the mouth of the channel, take up distinct routes.…”
Section: Possible Scenarios Of Development Of Lobe Complexesmentioning
confidence: 99%
“…Outcrop examples of turbidite systems show that lateral or oblique slope can represent a fundamental guide on flow pattern and on facies and lithology distribution in fan lobes (Kneller et al 1991;Sinclair 1994;Sinclair and Tomasso 2002;Amy et al 2004;Sixsmith et al 2004;Smith and Joseph 2004;Tomasso and Sinclair 2004;Shultz and Hubbard 2005;Amy et al 2007;Vinnels et al 2010;Bernhardt et al 2011). Moreover, laboratory experiments have investigated the effects of lateral and oblique slopes on flow behavior and on the resultant depositional processes (Kneller et al 1991;Kneller 1995;Amy et al 2004).…”
Section: Introductionmentioning
confidence: 99%